African Ancestry. Rhythm and Orality in Toques de Son Colorá - Salinas Herrera, Lilian Joscelyne (2023)
The following article analyzes the centrality that rhythm acquires in the novel Toques de Son Colorá (2020) by the Colombian writer Adelaida Fernández Ochoa. The objective is to demonstrate that the relevance of this component arises linked to the oral tradition, which in turn is linked to the ancestral African roots present both in the biography of the author and throughout the American continent, so they permeate the entire narrative. Specifically, the relevance of the musical genre of salsa along with other Caribbean rhythms within the plot of the novel will be addressed as examples of the presence of that ancestral heritage in the contemporary context of the work. At the same time, this analysis will be guided mainly by the studies on this component developed by the Peruvian researcher Victoria Santa Cruz Gamarra, together with various Afro-centered theoretical proposals that address the concept of orality. We see that in this work this component arises twinned with that of writing, allowing with this to expand the investigations already carried out on Afrodescendants and their role in both Colombian and Latin American identity, considering the approaches obtained from the intersection between gender and race present in the novel.